Dilemme du verbal versus visuel: Analyse des images dans L’Homme aux valises d’Ionesco - Lukovszki, Judit (Verbum – Analecta Neolatina, 2006)
There is a tendency these days that makes us move away from the text to the direction of performance. The distinguished role of the text is becoming weaker; interest is focused on forms of expression that also stimulate our senses. The relation between the writer Ionesco and this tendency is close. Temporally considered, writing gives its place to messages which are made for the eyes: the ageing Ionesco is losing his belief in the power of the text, he only creates paintings near the end of his life. Also, sacred Christian, Tibetan, zen, etc. texts teach him the respect of silence. And silence gives place to images. This paper presents these issues with the help of an interpretation of one of Ionesco’s plays, written in 1975, L’homme aux valies.